KINERJA KARYAWAN DITINJAU DARI KEPEMIMPINAN, LINGKUNGAN KERJA, DAN DISIPLIN KERJA PADA SHOWROOM MUHARI MOTOR 651 KARANGANYAR - Fiya Mila Fatmawati; Sri Hartono; Istiatin Istiatin (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to support leadership, work environment and work discipline on the performance of employees of the Muhari Motor 651 Karanganyar Showroom. This research uses quantitative descriptive. The population in this study were all 116 participants and the sample used was 90 respondents by distributing questionnaires. Data were analyzed using SPSS version 21, hypothesis testing using multiple linear regression analysis. With the approved questionnaire questions declared valid and reliable. In the classical research assumptions test produces normal data, there is no multicollinearity and heteroscedasticity does not occur. From the results of the F test stated that the variables of leadership, work environment and work coordination determine simultaneous and significant impact on employee performance at the Muhari Motor 651 Karanganyar Showroom with a Fcount of 126.690> Ftable 3.101 and a significant value of 0.000 ttable 1.988 significant value 0.000 t table1.988 and a significant value of 0.000